Penegakan Hukum Terhadap Pelaku Tindak Pidana Judi Online (Studi Kasus Proses Tindak Pidana Kasus Judi Online di Wilayah Hukum Kepolisian Daerah Jawa Timur) - Fahrul, Fahrul (Jurnal Ilmiah Wahana Pendidikan, 2024)
With advances in technology, it is not impossible for crimes to occur in the field of technology, especially in cyberspace. The crime that is often committed in cyberspace is online gambling. This research aims to analyze law enforcement against perpetrators of online gambling crimes in the jurisdiction of the East Java regional police and to analyze the application of criminal sanctions against perpetrators of online gambling crimes in the jurisdiction of the East Java regional police. This research uses normative juridical research methods, with a case approach and a statutory approach. The data collected came from legal material sources, and data collection was also carried out using literature studies which were processed using qualitative methods. The results of the research show how the East Java Regional Police, Sub-Directorate V Cyber, Ditreskrimsus, are involved in law enforcement for online gambling suspects from the arrest process until they are sentenced, namely related to Information and Transactions. The perpetrator deliberately and without right distributes funds or transmits funds or makes electronic information about funds or electronic documents containing gambling content accessible as intended in Article 27 paragraph (2) in conjunction with Article 45 paragraph (2) of Law no. 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, and/or Article 303 of the Criminal Code.